Does my head look big in this? - Abdel-Fattah, Randa (New York : Orchard Books, 2007)
Year Eleven at an exclusive prep school in the suburbs of Melbourne, Australia, would be tough enough, but it is further complicated for Amal when she decides to wear the hijab, the Muslim head scarf, full-time as a badge of her faith--without losing her identity or sense of style.
850
Keywords: Hijab (Islamic clothing) -- Juvenile fiction; Muslims -- Australia -- Juvenile fiction; High schools -- Juvenile fiction; Islam -- Customs and practices -- Juvenile fiction; Clothing and dress -- Juvenile fiction; Young adult fiction; Australia -- Juvenile fiction